Pengaruh Variasi Produk, Persepsi Kemudahan Penggunaan, dan Harga terhadap Kepuasan yang Berdampak pada Loyalitas Konsumen Disney+ Hotstar - Muhammad Akbar; Vina Meliana (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
Technological advancements enable media and entertainment companies to reach customers more easily and generate more revenue. Using a quantitative method with purposive sampling technique, this study aims to determine the impact of product variety on customer satisfaction, the influence of user-perceived ease of use on customer satisfaction, the influence of price on customer satisfaction, and the impact of satisfaction on customer loyalty towards the object of SvoD Disney+ Hotstar. Multiple linear regression analysis is employed. The research findings indicate that product variety does not affect customer satisfaction; user-perceived ease of use influences satisfaction; price affects satisfaction; and customer satisfaction influences customer loyalty